Application of Kansei Engineering to Capture Consumer Demand for Cooking Oil Product Packaging - Komang Nickita Sari; Maria Anityasari; Ni Ketut Sari; I Komang Tri Musthika (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
Plastic food packaging has become a part of human daily life. The management of plastic waste is a matter of concern due to its potential which is difficult to decompose. This condition causes all producers to have a responsibility not only during the manufacturing process but until the end of the life of their products. This expanded responsibility is called EPR (Extended Producer Responsibility). Therefore the resulting packaging design becomes a breakthrough in this matter. This research attempts to apply the Kansei Engineering method to capture customers' emotional needs from consumers in compiling plastic packaging design parameters. The research method in this paper uses the Kansei Engineering method, namely by collecting Kansei words from respondents at random, then the Kansei words are reduced. The reduced Kansei word will be synthesized to produce quality attributes that are able to meet the customer's emotional needs. The Kansei words obtained from the survey results are 55 words. Packaging quality attributes that have met the customer's emotional needs include protection, refillable, recyclable, biodegradable, food safety, additional function, attractiveness, conformity, ergonomic, user friendly, and content declaration (on the packaging label).